(untitled) (Community Based Medical Journal, 2015)
Congenital heart disease is a defect in the structure of heart and great vessels present at birth. Early recognition will help to treat the child and if possible get corrective surgery done. The aim of this study was to observe the pattern of congenital heart disease in our set-up. This descriptive study based on echocardiographic findings over a period of 3 years from January 2013 to December 2015 conducted in Community Based Medical College Bangladesh, Mymensingh. Patient’s consent was obtained from patient’s parents before echocardiography. A total of 100 children found to have congenital heart disease determined by echocardiography were studied and analysed for frequencies of lesions, sex ratio and mean age. One hundred patients, comprising 55(55%) male and 45(45%) female had congenital heart disease as diagnosed by echocardiogram had, their age ranged from 0.01 to 15 years with a mean age of 6.4±5.3 years and male to female ratio 1.2:1. Sixty six percent of patients were diagnosed as non-cyanotic heart defects and rest 34% cyanotic heart defects. Atrial septal defect (35%) was the most frequent form of non-cyanotic congenital heart defect, followed by ventricular septal defect (15%), pulmonary stenosis (6%) patent ductus arteriosus (5%), endocardial cushion defect (3%) and coarctation of aorta (2%). Whereas fallot’s tetralogy (17%) followed by transposion of great arteries (10%) and ebstein’s anomaly (7%) were the commonest cyanotic congenital heart defects. Congenital heart diseases are common in our set-up. Atrial septal defect is the commonest non-cyanotic and Fallot’s tetrology as cyanotic congenital heart disease. CBMJ 2015 July: Vol. 04 No. 02 P: 20-26